2020
DOI: 10.3389/fimmu.2020.01827
|View full text |Cite
|
Sign up to set email alerts
|

Impact of N-Acyl-Homoserine Lactones, Quorum Sensing Molecules, on Gut Immunity

Abstract: Among numerous molecules found in the gut ecosystem, quorum sensing (QS) molecules represent an overlooked part that warrants highlighting. QS relies on the release of small molecules (auto-inducers) by bacteria that accumulate in the environment depending on bacterial cell density. These molecules not only are sensed by the microbial community but also interact with host cells and contribute to gut homeostasis. It therefore appears entirely appropriate to highlight the role of these molecules on the immune sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 69 publications
1
41
0
Order By: Relevance
“…Again, these in vitro observations need to be interpreted with caution as non-physiological concentrations of oxo-C 12 -HSL were used in the studies using immortalized cell line. A more detailed review of modulation of gut immunity by QS molecules can be found here[ 376 ].…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Again, these in vitro observations need to be interpreted with caution as non-physiological concentrations of oxo-C 12 -HSL were used in the studies using immortalized cell line. A more detailed review of modulation of gut immunity by QS molecules can be found here[ 376 ].…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Many tiers of factors are assumed to govern the LuxR-centered QS output for various collective phenotypes, e.g. the upstream autoinducer signaling cascades of luxR expression, the DNA binding sites and their distribution in genes, and the manner by which LuxR interacts with specific DNA ( 45–48 ). Although further analysis of the signaling dynamics of the QS input is warranted, conserved QS components, such as LuxO, qrr s, and AphA, have been identified, demonstrating that V. alginolyticus harbors QS systems resembling that of V. harveyi ( 12 , 18 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…when the concentrations of signaling molecules reach a critical threshold, the result is modulation of certain target genes that trigger the formation of biofilms [37]. In Gram-negative bacteria, N-acyl-homoserine lactones (AHL) have been identified as the major signaling molecules in this communication system [38][39][40]. Considerable evidence suggests that PON1 plays an important role against biofilm formation.…”
Section: Paraoxonase-1 Is An Antioxidant Enzyme That Participates In mentioning
confidence: 99%